Intake of Fortification of Lumbricus rubellus Flour and Eucheuma cottonii Flours on Egg Weight, Consumption and Conversion of Laying Hens Feed - Muchlis, Ahmad; Hasyim, Zohra; Aqmal, Amal; Asmawati, Asmawati; Firdaus, Firdaus (AgriSains, 2019)
This study aims to determine the effect of Lumbricus rubellus flour and Eucheuma cottonii flour on egg weight, consumption and feed conversion of laying hens. The material used in this study was a 48 week-old laying hen (productive egg laying), given additional L. rubellus flour and E. cottonii flour with different levels into basal feed. Complete Randomized Design Analysis (CRD) shows the positive effect of flours on egg weight, feed consumption and conversion to laying hens.